Effects of Melamine in Young Pekin Ducks - Landers, B.R.; Murarolli, R.A.; Gelven, R.E.; Brand, L.M.; Ledoux , D.R.; Bermudez, A.J.; Rottinghaus, G.E. (International Journal of Poultry Science, 2012)
An experiment was conducted with male Pekin ducks to determine the toxicity of melamine (MEL) in young ducks fed dietary treatments from hatch to 21 days of age. Two hundred day-old male ducks were purchased from a commercial hatchery and assigned to one of ten treatment groups. Each treatment group consisted of five replicates with four ducks per replicate group. The diets contained 0.0, 0.25, 0.50, 0.75, 1.0, 1.25, 1.50, 1.75, 2.0 and 2.25% MEL. Compared with controls, ducks fed > 1.0% MEL had reduced feed intake and body weight gain (P<0.0001). Compared to controls, relative kidney weights were higher (P<0.0001) in ducks fed diets containing > 1.0% MEL. Compared with controls, ducks fed > 0.25% MEL had increased (P<0.0001) kidney MEL concentrations, whereas ducks fed > 0.75% MEL had increased (P<0.0001) muscle concentrations of MEL. MEL concentrations in the bile increased as dietary inclusion increased. Renal histopathology of all ducks with treatment related deaths were uniform with moderate to severe multifocal accumulation of eosinophilic to basophilic mineralized casts within renal tubules and collecting tubules. Histopathology results suggest that > 1.5% MEL in the diet can cause severe renal pathology and mortality due to renal failure in ducks. The renal pathology observed in ducks was similar to that seen in other poultry species fed toxic concentrations of MEL.